Rapid and safe removal of foreign bodies in the upper esophagus in children using an optimized Miller size 3 video laryngoscope blade. Issue 5 (28th February 2021) - Kaufmann, Jost; Grozeva, Boyana; Laschat, Michael; Brackhahn, Michael; Rudolph, Diana; Neuhaus, Nikolas; Hubertus, Jochen; Wappler, Frank; Eich, Christoph
Abstract: Background: Foreign bodies lodged in the upper esophagus in children may result in life‐threatening complications, especially with button batteries. Rapid removal is essential to prevent complications. Experts report that extraction with a suitable laryngoscope and a forceps is feasible under general anesthesia, but no further data had been available so far. Aims: To study foreign body visualization and removal from the upper esophagus in children using a new optimized Miller size 3 blade video laryngoscope. Methods: This prospective observational study was performed in three pediatric hospitals. The clinical observations were reported anonymously on an electronic spreadsheet after obtaining the informed consent from the parents or guardians. During the observational period from January 2019 to October 2020, all children with a foreign body lodged into the upper esophagus were eligible for participation and 22 cases were included. Main outcome measures were rates of successful removal and complications as well as duration of the procedure. Secondary outcome was subjective assessment regarding the quality of the visualization and the feasibility of the procedure. Results: Success rate was 100% with no complications. Mean intervention and anesthesia times were 5 ± 4 minutes and 26 ± 25 minutes. Quality of visualization of the foreign body was judged as 'excellent' or 'good' in all cases and the feasibility of the procedure as 'without' or 'with little' effort in 95% of all cases. Conclusion: The new Miller size 3 video laryngoscope enables rapid, easy, and reliable extraction of foreign bodies when they are located in the upper part of the esophagus. As early removal of esophageal foreign bodies, especially with button batteries, prevents life‐threatening complications, we suggest this technique as the first choice of treatment.